2005
DOI: 10.1088/0953-8984/17/27/010
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-elastic scattering, random fields and phonon-coupling effects in PbMg1/3Nb2/3O3

Abstract: The low energy part of the vibration spectrum in PbMg 1/3 Nb 2/3 O 3 (PMN) relaxor ferroelectric has been studied by means of neutron scattering above and below the Burns temperature, T d . The transverse acoustic and the lowest transverse optic phonons are strongly coupled and we have obtained a model for this coupling. We observe that the lowest optic branch is always underdamped. A resolution-limited central peak and quasi-elastic scattering appear in the vicinity of the Burns temperature. It is shown that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(112 citation statements)
references
References 43 publications
(49 reference statements)
6
104
2
Order By: Relevance
“…In the absence of disorder and in the classical limit ( → 0), we recover the standard results for conventional ferroelectrics. 31 The line shape of the structure factor (13) resembles that of the well-known Lorentzian plus Lorentzian squared for disordered magenetic systems 38 with the important distinction that the relevant interactions in our problem are long-ranged and anisotropic dipolar forces rather than short-ranged isotropic exchange interactions.…”
Section: Solution By Onsager Cavity Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…In the absence of disorder and in the classical limit ( → 0), we recover the standard results for conventional ferroelectrics. 31 The line shape of the structure factor (13) resembles that of the well-known Lorentzian plus Lorentzian squared for disordered magenetic systems 38 with the important distinction that the relevant interactions in our problem are long-ranged and anisotropic dipolar forces rather than short-ranged isotropic exchange interactions.…”
Section: Solution By Onsager Cavity Methodsmentioning
confidence: 79%
“…We now compare the static structure factor S q with that measured by neutron scattering experiments 13,14 . Without compositional disorder (∆ = 0), simple inspection shows that S q=0 diverges as the mode frequency softens in the vicinity of the critical point T c where long-range ferroelectric order sets in.…”
Section: Resultsmentioning
confidence: 99%
“…8 Dielectric measurements have found the presence of a frozen glassy state at low temperatures and have led to theories of random bond and field effects in analogy to the case of spin glasses. [9][10][11][12] Recent neutron and x-ray scattering studies conducted on PMN and PZN in zero field have found no long-range structural distortion in the bulk at low temperatures. This new phase ͑referred to as phase X in the original measurements͒ was first measured and presented based on neutron diffraction measurements on PZN doped with 8% PT.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 For PMN the intensity associated with the QE scattering was found to follow the temperature dependence of the dielectric permittivity. 8 The central peak ͑CP͒ and the QE component are also observed in doped PMN by neutron scattering, 9 although the CP intensity is weaker than in pure PMN. In ͑1−x͒PMN− xPT with x = 0.32 the susceptibility of the QE scattering increases below the Burns temperature and has a broad maximum at the temperature where the cubic-totetragonal phase transition occurs.…”
mentioning
confidence: 93%
“…We present an analysis of the evolution of the intensity and of the linewidth of this component as a function of the temperature and compare the results with those obtained in ͑1−x͒PMN− xPT ͑x = 0 and x = 0.32͒. 8,9 We used the cold neutron three-axis spectrometer TASP ͑Ref. 14͒ ͑SINQ, 15 PSI͒ operated in the constant k f -mode with k f = 1.64 Å −1 .…”
mentioning
confidence: 99%